ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI PERTUMBUHAN LABA PADA PT. ANEKA TAMBANG Tbk - Artika Handayani; Nafisah Nurulrahmatia (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
The aims of this study was to examine the effect of net profit margins on profit growth at PT. Aneka Tambang Tbk. The population used is the financial statement data from 1997-2018. With a sample of research for 7 years namely 2012-2018. The method used is purposive. The type of data is secondary data sourced from financial statements. The data analysis method used is a simple linear regression analysis. Hypothesis testing results, Net Profit Margin (NPM) has no significant effect on profit growth.